(untitled) (Journal of Environmental Bioremediation and Toxicology, 2014)
Copper (II) complex of 4-azomalononitril antipyrine has been isolated and characterized basedÂ on IR spectra, 1H NMR, elemental analyses, molar conductance, electronic spectra and magneticÂ moment. A diminished amount of antioxidant enzyme coupled with superoxide production in appears to be general characteristic of the tumor cells. This character can be used in cancerÂ treatment. The present study attempted to investigate the effect of copper (II) complex of 4-Â azomalononitril antipyrine which has SOD like activity on tumor development using EhrlichÂ ascites carcinoma (EAC) implemented in Swiss albino female mice. The results showed thatÂ copper complex with ligand has anti cancer activity in all studied parameters with variable ratios.